EFFECTS OF QUERCETIN AS AN EXTENDER-ADDITIVE ON CRYOPRESERVATION OF GIR BULL SEMEN - PRAJAPATI, S G; VALA, K B; SOLANKI, G B; SINGH, V K; CHAVDA, B P (The Indian Journal of Animal Reproduction, 2021)
The present investigation was undertaken on semen of four mature healthy Gir bulls (4-6 years) maintainedidentically on University farm, Junagadh (India) during hot summer months. Semen collected using AV, soon afterroutine evaluation, was diluted with extender Andromed containing Quercetin as an antioxidant, viz. 0 μM (control),50 μM, 100 μM and 200 μM level, filled in French medium straws and frozen with conventional system. The sampleswere evaluated for sperm quality parameters and oxidative markers, viz., LPO/MDA and GST activity in seminalplasma at per-freeze (post-equilibrium) and post-thaw stage of cryopreservation. The mean pre-freeze values ofindividual sperm motility, viability, HOS reactive sperm and acrosomal integrity (75.58±1.07, 77.88±0.99, 65.88±0.31and 81.46±0.29 %, respectively) in 100 μM Quercetin group were significantly (p
Keywords: Cryopreservation; Gir bull semen; Oxidative markers; Quercetin; Sperm quality parameters